2013
DOI: 10.1093/cid/cit234
|View full text |Cite
|
Sign up to set email alerts
|

A Risk for Hepatocellular Carcinoma Persists Long-term After Sustained Virologic Response in Patients With Hepatitis C–Associated Liver Cirrhosis

Abstract: The risk for HCC, liver decompensation, and death in patients with liver cirrhosis related to HCV was markedly reduced after SVR, but a long-term risk of developing HCC remains for up to 8 years. Cirrhotic patients with HCV who achieve SVR should therefore maintain long-term surveillance for HCC. Future studies aimed to better identify those with remaining long-term risk for HCC are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
215
2
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 217 publications
(236 citation statements)
references
References 22 publications
11
215
2
8
Order By: Relevance
“…However, the proportion with continued excessive alcohol consumption after HCV diagnosis is unknown. In a previous study, the risk for decompensation and liver-related death after achieving SVR was low in cirrhotic patients in Sweden [51], potentially indicating limited impact of this comorbidity.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…However, the proportion with continued excessive alcohol consumption after HCV diagnosis is unknown. In a previous study, the risk for decompensation and liver-related death after achieving SVR was low in cirrhotic patients in Sweden [51], potentially indicating limited impact of this comorbidity.…”
Section: Discussionmentioning
confidence: 85%
“…Another limitation is that the model does not consider the decreased but remaining risk of HCC and disease progression among cirrhotic patients that achieved SVR [51]. This may result in an underestimation of future burden of disease and overstate the potential impact of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the incidences of CKD, DM, CVD, and death were 5.32 (95 % CI 3.99-6.98), 10.13 (95 % CI 8.20-12.37), 6.79 (95 % CI 5.26-8.65), and 13.49 (95 % CI 11.29-16.0) per 1000 PYFU, respectively. Kaplan-Meier curves showing the occurrence of extrahepatic events and deaths according to the study groups are reported in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…HIV/hepatitis C virus (HCV)-coinfected patients have accelerated progression of HCV-related liver disease and increased mortality rate compared to HCV-or HIV-monoinfected patients. There is increasing evidence that the achievement of sustained virologic response (SVR) after pegylated interferon (peg-IFN) plus ribavirin (RBV) treatment reduces the incidence of hepatocellular carcinoma (HCC), liver decompensation, and overall mortality in HIV/HCV-coinfected patients [3][4][5][6]. Although HCV coinfection is associated with an increased risk of cardiovascular disease (CVD), chronic kidney disease (CKD), and diabetes mellitus (DM) among HIV-infected patients, the impact of SVR on the risk of the development of extrahepatic complications has been little investigated [7][8][9].…”
Section: Introductionmentioning
confidence: 99%